1998
DOI: 10.1159/000007506
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide in Pathogenesis of Aspirin-Induced Gastric Mucosal Damage in Rats

Abstract: We examined the effect of NO synthase inhibitor on the functional and ulcerogenic responses to aspirin (ASA) in rat stomach. The animals were given ASA (20–80 mM) orally with or without HCl (10–50 mM) and killed 2 h later. NG-nitro-L-arginine methyl ester (L-NAME) was given i.v. 5 min before aspirin. In the functional study, a rat stomach was mounted on an ex vivo chamber under urethane anesthesia, perfused with saline, and transmucosal potential difference (PD), luminal pH, acid secretion and mucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 22 publications
2
31
1
Order By: Relevance
“…Prior study has established that neutrophil infiltration into gastric mucosal tissues is involved in the progress of acute gastric mucosal lesions [28]. The accumulation of neutrophil infiltration into the gastric mucosal tissues is estimated by MPO [29]. Furthermore, a reduction in the activity of MPO can be interpreted as a manifestation of the anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Prior study has established that neutrophil infiltration into gastric mucosal tissues is involved in the progress of acute gastric mucosal lesions [28]. The accumulation of neutrophil infiltration into the gastric mucosal tissues is estimated by MPO [29]. Furthermore, a reduction in the activity of MPO can be interpreted as a manifestation of the anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…The MPO assay has had widespread use as an index of neutrophil infiltration in various gastric injuries (23,26,44,45,55,56). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, lansoprazole and ranitidine also increased MPO activity. It has been reported that the release of MPO from gastric cells is another indication of the degree of ulceration, with NSAIDs such as indomethacin also exerting their effects via inhibition of MPO pathways (23,26,44,45,55,56). Tissue MPO activity is a sensitive and specific marker of acute inflammation and reflects polymorphonuclear cell infiltration into the parenchyma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NO has cytoprotective properties 1,46,47 in the stomach and other organs that are derived from its ability to increase local blood flow and to scavenge destructive free radicals. 48,49 New classes of NSAIDs that release NO, called NO-NSAIDs, have been developed and have been shown to be safe and effective alternatives to conventional NSAIDs. 49 -52 These agents are composed of two classes of compounds, one that contains a nitrate ester functionality 50 -52 and one that contains an S-nitrosothiol functionality.…”
Section: Bifunctional Donorsmentioning
confidence: 99%